PENGARUH SULFAT PADA KEKUATAN BETON YANG MENGGUNAKAN LIMBAH BATU BARA SEBAGAI BAHAN PENGGANTI SEMEN - Randy Setiawan; Fera Lestari; Dian Pratiwi (Jurnal Teknik Sipil, 2017)
Many industries meet the electricity needs by establishing their own Steam Power (power plant) coal-fired. Burning coal produces waste in the form of fly ash (fly ash) in very much. Therefore, this study uses fly ash concrete-making materials such as cement replacement.   In  this  research,  test  the  strength  of  normal  concrete  and  geopolymer  concrete  cube  measuring  15  x 15 X15 cm 3. Materials used in this study were sand (fine aggregate), gravel / split (coarse aggregate), water, NaOH  solution,  fly  ash  /  fly  ash,  cement,  alkaline  activator  is  a  solution  of  sodium  silicate,  sodium hydroxide, sulfate and water. Measurement of compressive strength of geopolymer concrete and ordinary concrete  with  each  of  treated  water  tidal  sulfate  (treatment  on  ferrocement  tanks)  and  untreated  water tidal  sulfate  at  daily  intervals  to  the  1st,  7th,  14th,  21st  ,  to-28.  Each  daily  intervals  used  5  pieces  of concrete. Analysis of the data used is the ratio between the compressive strength of ordinary concrete and geopolymer.   Conclusion of this research is fly ash can be used instead of 100% cement to mix concrete. Sulfuric affect the  strength  of  normal  concrete.  While  on  geopolymer  concrete  sulfate  solution  has  not  yet  affected  the strength of concrete.